The Effectiveness of Rehabilitation Centers on the Psych emotional State of Children of the First Period of Childhood with Congenital Cleft Lip and Palate (Eurasian Medical Research Periodical, 2022)
The purpose of the study is to identify the effectiveness of rehabilitation centers on the psycho-emotional state of children in the first period of childhood with congenital cleft lip and palate. The study showed that specialized rehabilitation centers are very convenient for parents of a child with CCLP, who find it difficult to care for and develop a child after undergoing surgical manipulations. SRC for children with CCLP has proven to have an effective impact on the child not only psycho-emotionally but also on the physical development of the child. The children were divided into 2 groups, group I consisted of children with CCLP who did not use the services of the SRC, group II consisted of children who applied to the SRC after surgical manipulations. In the II group of children, the children were calmer and gained weight, and in the I group of children no changes were detected